Perceptions of Faculty Members on Empathy in Higher Education in Azerbaijan - Mammadova, Nazrin; Mammadova, Gunel; Ibrahimova, Nigar; Gudrat, Madina (ADA University, 2025)
This research study aimed to explore the perceptions and experiences of faculty members on empathy. The study focused on two main research questions to identify definitions of empathy and faculty experiences in building relationships in higher education in Azerbaijan. To gather comprehensive data, a qualitative approach and convenience sampling strategy was used. The sample size consists of nine faculty members from three public universities in Azerbaijan. The main selection criteria of participants involved having at least five years of experience in various academic departments in higher education. To get accurate analysis, semi-structured interviews were audio-recorded and video-recorded. During the data analysis, member check and peer review were used to ensure that the participants’ perspectives and the correctness of the translations were accurately represented. The findings of the research reveal the perceptions and experiences on empathy from both male and female perspectives. The data mostly focuses on how empathy affects teaching strategies, relationship with students and colleagues in higher education. Besides, the research indicates that the definition of empathy varies differently among faculty members from humanitarian and technical fields. On the other hand, there had some limitations including limited sample size, gender biases, language barriers and time constraints. As a final recommendation, we came up with a booklet, which indicates different ways to foster empathy and highlight empathetic teaching strategies in higher education
Keywords: Empathy -- Study and teaching (Higher) -- Azerbaijan.; College teachers -- Attitudes -- Azerbaijan.; College teachers -- Interpersonal relations -- Azerbaijan.; Education, Higher; Education